STUDI HOMOLOGI DAERAH TERMINAL-C HASIL TRANSLASI INSCRIPTO BEBERAPA GEN DNA POLIMERASE - MULYONO
DNA polymerase plays an important role in DNA replication process. Commonly the enzyme has three activities, i.e. 5\'--+3\' polymerase, 5\'-*3\' exonuclease and 3\'->5\' exonuclease which localized in three different domains. Orderly the polymerase activity lies on the Cterminal domain, followed by 3\'->5\' and 5\'-+3\' exonuclease activity domain on the N-terminal. Information concerning amino acid sequences on the C-terminal region is important for structure-function studies of the polymerase activity. Homology studies on DNA polymerases from different sources by observed on the sequence of the terminal amino acids have been conducted. C-terminal region of DNA polymerases (from GenBank i.e. NCBI) were compared which resulted in 2 conserved amino acid regions i.e. DPNLQNIP and QVHDELL. These regions which located on the C-terminal of DNA polymerase has one gap around 200 amino acids. One set of primer pairs were designed to amplify DNA fragment on the above region. Twelve out of fourteen of DNA samples, isolated from different organisms, were amplified by FP1 and PUR1 primers which resulted in 0.6 kb fragments. These fragments were cloned on pGEM-T vector using E. colt JM 109 as it\'s host. Restriction analysis on the recombinant plasmids suggested that the fragment were succesfully ligated. Further analysis based on nucleotide sequencing suggested that the fragments length were between 639 to 645 base pairs. All sequences were in frame with the published DNA polymerase. Inscripto translation and amino acids comparison among the fragments indicated that the sequences were relatively different. However, one out of three acidic amino acids that presumed has an important role on this region was very conserved as well. Comparison of the same region of DNA polymerases with the published data suggested that the organisms within a genus has specific pattern of amino acid sequences.